Red Spinach (Alternanthera amoena voss) as an Environmental Friendly Acid Base Indicator - Sri Adelila Sari; Suriati Nilmarito (Universitas Negeri Medan, 2019)
Natural indicators are indicators that are continuously developed to determine whether a sample is acidic or basic. This study examined how red spinach can be developed into an environmentally friendly acid-base indicator that intends to be non-toxic, easy to obtain, and affordable. The natural indicator used in this study was red spinach leaf extract (Alternanthera amoena voss). The samples used were salt water, tea, pineapple, detergent, and oranges. Red spinach leaf extract was dropped on each sample which had a volume of 150mL resulting in a color change. The results of this study indicated that red discoloration occurs in samples of salt water, tea, oranges, and pineapples according to their acidic properties. Furthermore, detergent water turned to a bluish green color, and according to the basic properties of a detergent. This study concluded that red spinach leaf extract can be used as an environmental friendly natural indicator.